Institutions and economic policies for pro-poor agricultural growth - Dorward, Andrew R.; Fan, Shenggen; Kydd, Jonathan; Lofgren, Hans; Morrison, Jamie; Poulton, Colin; Rao, Neetha; Smith, Laurence; Tchale, Hardwick; Thorat, Sukhadeo; Urey, Ian; Wobst, Peter (International Food Policy Research Institute, 2004)
This paper draws together findings from different elements of a research project examining critical components of pro-poor agricultural growth and of policies that can promote such growth in poor rural economies in South Asia and Sub-Saharan Africa. Agricultural growth, a critical driver in poverty reducing growth in many poor agrarian economies in the past, faces many difficulties in today's poor rural areas in South Asia and Sub-Saharan Africa. Some of these difficulties are endogenous to these areas while others result from broader processes of global change. Active state interventions in 'kick starting' markets in 20th century green revolutions suggest that another major difficulty may be current policies which emphasize the benefits of liberalization and state withdrawal but fail to address critical institutional constraints to market and economic development in poor rural areas. This broad hypothesis was tested in an analysis of the returns (in agricultural growth and poverty reduction) to different government spending in India over the last forty years. The results reject the alternate hypothesis underlying much current policy, that fertilizer and credit subsidies, for example, depressed agricultural growth and poverty reduction in the early stages of agricultural transformation. The results show initially high but then declining impacts from fertilizer subsidies; high benefits from investment in roads, education and agricultural R&D during all periods and varying benefits from credit subsidies over four decades; low impacts from power subsidies; and intermediate impacts from irrigation investments. These findings demand a fundamental reassessment of policies espousing state withdrawal from markets in poor agrarian economies. Given widespread state failure in many poor agrarian economies today, particularly in Africa, new thinking is urgently needed to find alternative ways of 'kick starting' markets -- ways which reduce rent seeking opportunities, promote rather than crowd-out private sector investment, and allow the state to withdraw as economic growth proceeds. -- Authors' Abstract